Diabetes Mellitus Among Workers Exposed to Perfluorooctanoic acid - Spadini Putri; Muhammad Ilyas (ILUNI MKK FKUI and PRODI MKK FKUI, 2021)
Background: One of the health problems that can be caused by Perfluorooctanoic acid (PFOA) is Diabetes mellitus (DM). However, the causal relationship between Perfluorooctanoic acid and DM is still unclear, so it is necessary to look for some evidence regarding this relationship. The search for evidence is also equipped with a seven-step assessment of occupational diseases therefore it can assist occupational health doctors who find patients with DM and have a history of exposure to glutaraldehyde. Methods: Literature search using Pubmed, Cochrane and JSTOR databases. The keywords used are “PFOA” OR “perfluoroalkyl substances” OR “perfluorooctanoic acid” AND “diabetes mellitus”. Article selection was performed using the defined inclusion and exclusion criteria. Selected articles will be critically reviewed based on etiological studies from the Oxford Center of Evidence-Based Medicine. Result: It was in 5 selected articles that met the inclusion and exclusion criteria. The main finding after a critical review was that PFOA may increase the risk of DM. Conclusion: There is a relationship between PFOA and the incidence of DM in health workers. To establish the diagnosis of occupational diseases in health workers who are exposed to PFOA, seven steps of diagnosis of occupational diseases are used.